GMO Regulation in Brazil: Approximations to the EU or the USA Model? - Pizella, Denise Gallo [UNESP]; Souza, Marcelo Pereira de (Univ Federal Parana, Editora, 2016)
There are two main regulatory GMO models influencing various nations in their management procedures: a more flexible one, which is based on the Substantial Equivalence criterion and has in the United States of America its exponent, and another, more precautionary, based on the European Union. Given the existence of the two above-mentioned regulatory models, the purpose of this article is to analyze which of them is used as a reference by the Brazilian regulatory system. Therefore, a review of the U.S. and European regulatory systems was performed and the Final Opinion Report of genetically modified cotton variety released in Brazil was analyzed. It was found that, although many questions were raised by some of its members and in the public hearing of transgenic cotton, CTNBio approved the use of the GMO without requesting further clarification. Thus, by not adopting precautionary management practices, the regulatory GMO system in Brazil resembles the U.S. model.
Keywords: transgenic; precautionary principle; substantial equivalence criterion